Tobacco, God, and Books: The Perils of Barbarism in Eighteenth-Century Korea. Issue 3 (16th September 2014) - Evon, Gregory N.
Abstract : Late eighteenth-century East Asia witnessed similar events with the Qianlong emperor's (r. 1736–96) literary inquisition in China, King Chŏngjo's (r. 1776–1800) fight against heterodoxy in Korea, and Matsudaira Sadanobu's (1759–1829) Ban on Heterodoxy ( Igaku no kin, 1790) in Japan. As is well known, Qianlong sought to destroy anti-Manchu writings, whereas Matsudaira sought to impose order by mandating the neo-Confucian orthodoxy of Zhu Xi (1130–1200) in elite education. Chŏngjo's activities are less understood, but equally significant. His own literary inquisition developed around threats Catholicism posed to the centrality of neo-Confucian orthodoxy, but it encompassed wider concerns over heterodox books imported from Qing China (1644–1911). What Matsudaira desired, Chŏngjo took for granted as defining Chosŏn (1392–1910) Korea's historic claim to guard civilization, and his fears over the threats of barbarism intensified as Catholicism and other forms of heterodoxy arrived via Qing China. This study examines Chŏngjo's response to those threats.